Safety and efficacy of liquid nitrogen spray cryotherapy in Barrett’s neoplasia – a comprehensive review and meta-analysis - Chandan, Saurabh; Bapaye, Jay; Khan, Shahab R.; Deliwala, Smit; Mohan, Babu P.; Ramai, Daryl; Dhindsa, Banreet S.; Goyal, Hemant; Kassab, Lena L.; Aziz, Muhammad; Kamal, Faisal; Facciorusso, Antonio; Adler, Douglas G. (Endoscopy International Open, 2022)
Background and study aims Barrett’s esophagus (BE) is a precursor condition to esophageal adenocarcinoma (EAC), resulting in transformation of the squamous epithelium of distal esophagus to columnar-lined epithelium with intestinal metaplasia (IM). Liquid nitrogen spray cryotherapy (LNSC) is a non-contact method of BE eradication and has been used both as primary and salvage therapy. We conducted a systematic review and meta-analysis to assess the safety and efficacy of LNSC.Methods We searched multiple databases from inception through December 2021 to identify studies on use of LNSC for Barrett’s neoplasia. Pooled estimates were calculated using random-effects model and results were expressed in terms of pooled proportions with relevant 95 % confidence intervals (CIs) of complete eradication (CE) of dysplasia(D), high grade dysplasia (HGD) and IM.Results Fourteen studies with 707 patients were included in our final analysis. Overall pooled rates of CE-D, CE-HGD and CE-IM were 80.8 % (CI 77.4–83.8; I2 62), 90.3 % (CI 85.2–93.7; I2 33) and 55.8 % (CI 51.7–59.8; I2 73) with follow up ranging from 4.25 months to 69.7 months. In patients with follow up beyond 24 months, the rates of CE-D and CE-IM were 83.6 % (CI 77.6–88.2; I2 60) and 54.7 % (CI 47.6–61.6; I2 81). Among LNSC naïve patients with prior history of endoscopic resection, the rates were 79.9 % (CI 73.3–85.2; I2 50) and 67.1 % (CI 59.5–73.8; I2 0). Pooled rate of therapeutic failures, defined as lack of response to LNSC therapy, was 23.6 % (CI 19.4–28.3; I2 73). Post LNSC strictures and perforation pooled rates were 4 % and 0.8 %, respectively, which are similar to those previously reported for RFA.Conclusions Our analysis suggests that liquid nitrogen spray cryotherapy is an acceptable treatment for BE in both ablation naïve and experienced patients.